The role of reason in the establishment of practical goals. A dialogue with some interpretations of Aristotle - Gómez, Laura (Estudios de Filosofía, 2022)
There is a current debate about the interpretation of the Aristotelian theory of action concerning the role of reason in the establishment of practical ends, given that in some passages Aristotle assigns to character the role of establishing ends, and in others he gives reason the role of government in the soul. How can these two groups of textual evidence be reconciled? In this article I will argue that these two types of evidence explain two different psychological phenomena. For this purpose, I will discuss the main and most recent interpretations in this debate (intellectualism, anti-intellectualism and indirect intellectualism), showing how, although character establishes our habitual representations, desires and actions, reason can question and oppose them, as we can see in the processes of character change.